2018
DOI: 10.1128/genomea.00377-18
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of the Butanoic Acid-Producing Bacterium Clostridium luticellarii DSM 29923, Used for Strong Aromatic Chinese Liquor Production

Abstract: The strictly anaerobic, Gram-positive bacterium Clostridium luticellarii, which has straight or slightly curved rod-shaped cells, polar endospores, and peritrichous flagella, is used for the production of strong aromatic Chinese liquors. C. luticellarii is able to produce butanoic acid. The draft genome sequence consists of 3.757 Mbp, including 3,632 predicted protein-encoding genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…CO 2 could be incorporated into acetate, n-valerate and/or n-caproate thereby improving carbon recovery in the chain elongation process. Increased relative abundance in chain-elongating conditions (0.5–2 g nZVI⋅L –1 ) was observed for C. luticellarii which may use the Wood-Ljungdahl pathway to take up electrons, H 2 and/or CO 2 coupled to chain elongation ( Poehlein et al, 2018 ; Petrognani et al, 2020 ). Caproiciproducens and Ruminococcaceae species were also enriched under these same conditions but their capability to utilize CO 2 /H 2 /electrons for chain elongation remains to be studied.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…CO 2 could be incorporated into acetate, n-valerate and/or n-caproate thereby improving carbon recovery in the chain elongation process. Increased relative abundance in chain-elongating conditions (0.5–2 g nZVI⋅L –1 ) was observed for C. luticellarii which may use the Wood-Ljungdahl pathway to take up electrons, H 2 and/or CO 2 coupled to chain elongation ( Poehlein et al, 2018 ; Petrognani et al, 2020 ). Caproiciproducens and Ruminococcaceae species were also enriched under these same conditions but their capability to utilize CO 2 /H 2 /electrons for chain elongation remains to be studied.…”
Section: Discussionmentioning
confidence: 98%
“…Hydrolyzed lactate seemed to be rapidly used for chain elongation since chain elongation products showed sustained production over time despite lactate monomers were depleted ( Figure 2 ). Several bacteria harboring genes involved in lactate oxidation (lactate dehydrogenases, Ldh) and the RBO pathway such as C. tyrobutyricum ( Wu et al, 2017 ), C. luticellarii ( Poehlein et al, 2018 ) and members of the family Ruminococcaceae ( Tao et al, 2017 ) including Caproiciproducens species (e.g., Bengelsdorf et al, 2019 ) were enriched in these conditions. C. tyrobutyricum is known as an efficient n-butyrate producer ( Wu et al, 2017 ) but is not reported to produce longer carboxylates.…”
Section: Discussionmentioning
confidence: 99%
“…So far, hydrogenotrophy and caproate production have not been reported as functions of C. luticellarii ( Wang et al, 2015 ). However, its genome harbors typical genes of the Wood-Ljungdahl pathway ( Poehlein et al, 2018 ) and C. luticellarii was the main candidate to elongate propionate to valerate and to produce i -butyrate in a recent study ( de Smit et al, 2019 ). Moreover, a caproate producer recently isolated in our laboratory, Clostridiales bacterium isolate BL-3, is also closely related to C. luticellarii ( Liu et al, 2020b , c ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no alcohols were detected throughout the operation time. Bacteria capable of performing homoacetogenesis such as Oscillibacter [46] and Clostridium luticellarii [47] were present in chain-elongating microbiomes. However, homoacetogenesis from H 2 and CO 2 did not seem likely to occur (∆G' <20 kJ•edonor −1 ) at the P H2 observed here (0.1 atm period I;~0.3 atm periods IV-V).…”
Section: Shift From MCC To Scc Production Was Unrelated To Hydrogen Partial Pressurementioning
confidence: 99%